2015
DOI: 10.1155/2015/184241
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Resveratrol against Human and Animal Viruses

Abstract: Resveratrol is a potent polyphenolic compound that is being extensively studied in the amelioration of viral infections both in vitro and in vivo. Its antioxidant effect is mainly elicited through inhibition of important gene pathways like the NF-κβ pathway, while its antiviral effects are associated with inhibitions of viral replication, protein synthesis, gene expression, and nucleic acid synthesis. Although the beneficial roles of resveratrol in several viral diseases have been well documented, a few advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 42 publications
1
111
0
6
Order By: Relevance
“…Resveratrol inhibits the replication of several viruses, including herpes simplex viruses (HSVs) 1 and 2, varicella-zoster virus, papillomaviruses, and influenza virus (9)(10)(11)(12). Topical application of resveratrol has been found to inhibit HSV vaginal transmission in mice, suggesting that it might be useful as a topical microbicide (13).…”
mentioning
confidence: 99%
“…Resveratrol inhibits the replication of several viruses, including herpes simplex viruses (HSVs) 1 and 2, varicella-zoster virus, papillomaviruses, and influenza virus (9)(10)(11)(12). Topical application of resveratrol has been found to inhibit HSV vaginal transmission in mice, suggesting that it might be useful as a topical microbicide (13).…”
mentioning
confidence: 99%
“…It has been reported that resveratrol and its derivatives possess antiviral activity with diverse mechanisms, including inhibition of viral protein synthesis or transcription and modulating viral related gene expressions or signaling pathways in host cells [Abba et al, ]. A number of studies have shown that resveratrol and its derivatives inhibit the replication of different viruses such as herpes simplex [Docherty et al, ], varicella‐zoster [Docherty et al, ], and influenza A [Palamara et al, ; Li et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Different polyphenols are active against several types of influenza virus (Table 2). Between them, RSV is well known for its antiviral effects against H1N1 type by blocking the nuclear-cytoplasmic translocation of the viral ribonucleoproteins and consequently by inhibition of the protein kinase C associated pathways (Abba, Hassim, Hamzah, & Noordin, 2015).…”
Section: Influenza Virusmentioning
confidence: 99%